Juridical Review of The Determination of National Territorial Boundaries According to The Provisions of International Law - Anggi Rokiba; Anis Rindiandi; Angga Aldilla Gusman (Jurnal Hukum dan Keadilan, 2026)
The increasing complexity of business activities in the era of globalization has heightened the potential for disputes among business actors. Business disputes may arise from breaches of contract, violations of agreements, differences in contractual interpretation, or conflicts related to the implementation of legal relationships in trade and investment activities. Dispute resolution through litigation is often considered less effective due to its lengthy process, high costs, and relatively complicated procedures. Therefore, a dispute resolution mechanism that can provide legal certainty, efficiency, and protection for the interests of the parties involved is needed. One of the most widely used mechanisms is arbitration. Arbitration is a method of resolving civil disputes outside the general court system based on a written agreement between the disputing parties. In Indonesia, arbitration is regulated under Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Arbitration offers several advantages, including a faster resolution process, confidentiality of disputes, the freedom to choose arbitrators with expertise in the relevant field, and decisions that are final and binding. This article aims to analyze the position of arbitration within the Indonesian legal system, examine its effectiveness as an alternative method of business dispute resolution, and identify the various challenges encountered in its implementation. The study employs a normative legal research method through statutory and conceptual approaches. The findings indicate that arbitration plays an important role in supporting effective and efficient business dispute resolution, although several obstacles remain in the implementation and enforcement of arbitral awards.